2013
DOI: 10.1039/c3cc45829f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of chelation enhanced fluorescence in complexes of cadmium(ii), and a possible new type of anion sensor

Abstract: The Cd(II) complex of adpa (N-(9-anthracenylmethyl)-N,N-di-(picolyl)amine) in MeOH-H2O has increased fluorescence intensity with [Cl(-)], a new type of anion sensor. The structure of [Cd(adpa)(NO3)2] has a proposed fluorescence-quenching π-contact between Cd and the fluorophore, while the Cl in [Cd(adpa)Cl2] disrupts the π-contact, restoring fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 16 publications
4
56
0
Order By: Relevance
“…21 Table 7. Bond Lengths and Angles of Interest in the Structure of 6 2 in solution, which results from the equilibrium 2Hg(cdpa) 2+ + 2OH − ⇆ Hg(cdpa) 2 2+ + Hg(OH) 2 at pH 7.0. The latter equilibrium accounts for the very small percentage of Hg II present as the mono-complex Hg(cdpa) 2+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Table 7. Bond Lengths and Angles of Interest in the Structure of 6 2 in solution, which results from the equilibrium 2Hg(cdpa) 2+ + 2OH − ⇆ Hg(cdpa) 2 2+ + Hg(OH) 2 at pH 7.0. The latter equilibrium accounts for the very small percentage of Hg II present as the mono-complex Hg(cdpa) 2+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2,3 In this paper, the coordination geometry of heavy d 10 metal ions and how the problem of distortion of the coordination geometry to produce long Hg−N or Ag−N bonds that lead to a PET effect and quenching of the fluorescence might be overcome are further considered.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chromic materials that reversibly change color by an external stimulus such as light, heat, pressure and pH, have attracted the interest of many researchers in recent years, especially in the area of sensors . Development of fluorescent probes for the selective detection of cations and anions has gained significant attention in the field of supra‐molecular chemistry owing to their vital roles in many physiological and environmental processes . Because of the high sensitivity, low cost and rapid response of the fluorescence technique, it is preferred over several other sensing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The use of complexes of metal ions coordinated to a PET (photo‐induced electron transfer) sensor for sensing anions has been reported recently The Cd II complex of the ligand adpa (see Figure for key to ligand abbreviations) was found to show a strong increase in fluorescence intensity on binding of Cl – , Br – , SCN – , and S 2 O 3 2– to the Cd II in its complex with adpa in solution (50 % CH 3 OH/H 2 O). The idea that the increase in fluorescence intensity was caused by weakening of fluorescence‐quenching Cd ··· C π contacts was supported by structural studies that showed that the Cd ··· C π contacts present in the Cd II adpa complex were greatly lengthened on coordination of the Cl – , Br – , SCN – , and S 2 O 3 2– as compared to the less covalently binding NO 3 – anion, or, as predicted by DFT calculation, coordinated water molecules . The more weakly π contacting coumarin fluorophore of cdpa yields Cd II complexes that do not respond with increases in fluorescence intensity on coordination of anions, since no π contacts are present to be disrupted .…”
Section: Introductionmentioning
confidence: 99%
“…The structures of [Pb(DB‐cyclen)(ClO 4 ) 2 ] ( 1 ), [Cu(DB‐cyclen)(ClO 4 ) 2 ] ( 2 ), [Ag(DB‐cyclen)(ClO 4 )] ( 3 ), and [Cd(DB‐cyclen)(ClO 4 )H 2 O]ClO 4 ( 4 ) were determined to aid in understanding the fluorescence and complex stabilities observed. DFT calculations were also carried out to help interpret the results obtained: these have been particularly helpful in past studies in understanding, in particular, the role of π contacts in quenching fluorescence …”
Section: Introductionmentioning
confidence: 99%